Pengaruh Penggunaan Media Pembelajaran Berbasis ICT Terhadap Motivasi dan Hasil Belajar IPA Siswa Kelas V SD Negeri 1 Laompo - Anidi Anidi; Arna Juwairiyah; Chairan Zibar L. Parisu; Fernandes Arung (Jurnal Kajian Pendidikan dan Cakrawala Pembelajaran, 2025)
This research is an experimental research with a quantitative approach. The purpose of this study is to determine: 1) The effect of the use of ICT-based learning media on students' science learning motivation. 2) The effect of the use of ICT-based learning media on science learning outcomes of grade V students of SD Negeri 1 Laompo. The results of the study showed that in the subject of Natural Sciences (IPA) with the experimental method there was an increase, namely, the average value obtained in the pre-test of the experimental class was 61.70 and the average pre-test value in the control class was 60.00 and after being given treatment the post-test results in the experimental class were 80.29 while the post-test results in the control class were 79.15. the increase that occurred between the experimental pre-test and the experimental post-test was 18.59 and the increase that occurred between the control class pre-test and the control class post-test was 19.15. The pre-test score in the experimental class has a minimum score of 47 and a maximum score of 75. The pre-test score in the control class has a minimum score of 44 and a maximum score of 75. The post-test score in the experimental class has a minimum score of 76 and a maximum score of 95, while the post-test score in the control class has a minimum score of 65 and a maximum score of 84. Based on the results of the observation of motivation before being given the application of ICT-based learning media, it appears that the motivation aspect has an interest with a success percentage of 4.46%, attention with a success percentage of 5.13%, concentration with a success percentage of 3.64%, perseverance with a success percentage of 5.04%. From the data above, an average of 18.27% can be obtained and the level of success achieved is incomplete. And after being treated, it appears that the aspect of student learning motivation has an interest with a success percentage of 7.56%, attention with a success percentage of 8.20%, concentration with a success percentage of 5.68%, perseverance with a success percentage of 9.55%. Based on these data, an average of 30.99% was obtained and the level of success achieved was complete.